2018
DOI: 10.1097/inf.0000000000001855
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Atazanavir in HIV-1-Infected Children Treated With Atazanavir Powder and Ritonavir

Abstract: Weight-band dosing of ATV + RTV plus optimized dual nucleos(t)ide reverse transcriptase inhibitors in young HIV-1-infected children achieved similar ATV exposure to that in adults; no unexpected safety findings occurred, and with the exception of lower virologic suppression in the lowest ATV CCQ, there was no apparent trend in virologic suppression across ATV CCQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The PRINCE I and PRINCE II trials showed that ATV powder formulation in combination with RTV liquid in children 3 months to <11 years and weighing 5 to <35 kg dosed in weight bands reached the target drug exposure levels. 61,65,66 Results from the PRINCE I and II trials together with IMPAACT P1020 and the modeling study by Hong et al supported the FDA approval of ATV/r doses in children (see Table 3 , Supplemental Digital Content 2 , http://links.lww.com/TDM/A324).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…The PRINCE I and PRINCE II trials showed that ATV powder formulation in combination with RTV liquid in children 3 months to <11 years and weighing 5 to <35 kg dosed in weight bands reached the target drug exposure levels. 61,65,66 Results from the PRINCE I and II trials together with IMPAACT P1020 and the modeling study by Hong et al supported the FDA approval of ATV/r doses in children (see Table 3 , Supplemental Digital Content 2 , http://links.lww.com/TDM/A324).…”
Section: Methodsmentioning
confidence: 82%
“…5860 Safety data from a large cohort study on ATV/r in children also show increasing incidence and severity of hyperbilirubinemia with increasing C trough . 61 Because in this case the increase in bilirubin is not a product of liver damage but rather because ATV interacts with bilirubin conjugation, this effect is benign. Advantages of therapy should be weighed against potential stigmatizing side effect of icteric eyes from an increase in unconjugated bilirubin.…”
Section: Methodsmentioning
confidence: 99%
“…Dosage forms used with children must be palatable and must permit flexible dosing to accommodate reasonable precision over the large range of doses that are required. Use of dosing bands, by assigning children over a range of weights to the same dose, allows use of capsules or tablets that may be more stable to be used in cases in which some flexibility in dosing is permissable …”
Section: Dosage Formsmentioning
confidence: 99%
“…Use of dosing bands, by assigning children over a range of weights to the same dose, allows use of capsules or tablets that may be more stable to be used in cases in which some flexibility in dosing is permissable. 35,40 The relative bioavailability between the different dosage forms must be known so that as children are switched, the required dosing is maintained. Stability information is also required for all dosage forms and understanding of the impact of excursions in temperature, such as when doses are not refrigerated.…”
Section: Dosage Formsmentioning
confidence: 99%